The Influence of Age and Work Experience on Lumbar Spine Pain among the Nursing Staff - Anna Antczak-Komoterska; Lilla Nowakowska; Beata Haor; Dorota Kochman (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Currently, back pain syndromes are considered to be widely known problems in the medical, but above all, social and economic aspects. The specific nature of the profession performed by nurses puts them among the people most at risk of spine dysfunction.